USING MULTIMEDIA TOOLS IN SHAPING HISTORICAL THINKING OF STUDENTS IN THE MODERN EDUCATIONAL SYSTEM - Muhammadiyev Javlon Hayitboyevich (European Science Publishing, 2025)
In the modern educational process, the use of multimedia technologies for the development of students' historical thinking is of great importance for enhancing the effectiveness of learning activities. This article analyzes the role of multimedia technologies in the development of students' historical thinking. It examines the possibilities of acquiring historical knowledge through multimedia tools such as interactive presentations, video lessons, animations, and digital maps. The article also explores the impact of multimedia technologies on the development of students' analytical thinking, understanding of cause-and-effect relationships between historical events, and the formation of independent thinking skills. Practical recommendations and methodological approaches for educators are provided.
Keywords: Multimedia technologies, historical thinking, educational process, interactive learning, information and communication technologies, methodology, historical analysis, educational technologies, digital resources, independent thinking.